Momordin Ic induces G0/1 phase arrest and apoptosis in colon cancer cells by suppressing SENP1/c-MYC signaling pathway - Fang Xianjun; Xian Xirui; Tang Jie; Mu Huiwen; Zheng Shaojun; Ling Qiaoyun; Liu Yunxin; Sun Xuqun (Elsevier, 2021)
Momordin Ic (MI) is a natural pentacyclic triterpenoid enriched in various Chinese natural medicines such as the fruit of Kochia scoparia (L.) Schrad. Studies have shown that MI presents antitumor properties in liver and prostate cancers. However, the activity and potential mechanisms of MI against colorectal cancer remain elusive. Here, we showed that MI inhibited cell proliferation with G0/1 phase cell cycle arrest in colon cancer cells. Moreover, it was observed that MI increased apoptosis compared to untreated cells. Further investigation showed that the SUMOylation of c-Myc was enhanced by MI and led to the down-regulated protein level of c-Myc, which is involved in regulating cell proliferation and apoptosis. SENP1 has been demonstrated to be critical for the SUMOylation of c-Myc. Meanwhile, knockdown of SENP1 by siRNA abolished the effects of MI on c-Myc level and cell viability in colon cancer cells. Together, these results revealed that MI exerted an anti-tumor activity in colon cancer cells via SENP1/c-Myc signaling pathway. These finding provide an insight into the potential of MI for colon cancer therapy.